Traumatic Suprahepatic inferior vena cava injury survival of a rare case. (December 2021) - Rooke, Douglas A.; Burke, Christopher R.; Bulger, Eileen M.; Van Eaton, Erik; Nandate, Koichiro
Abstract: Traumatic supra-hepatic inferior vena cava (IVC) injury is rare and nearly universally fatal. We report an excellent outcome from a case involving severe injury of the suprahepatic and intra-pericardial IVC utilizing emergency cardiopulmonary bypass (CPB) with deep hypothermic circulatory arrest. The goal of this case report is to outline key factors that facilitated the patient's survival of extensive IVC injury. We conclude that aggressive prehospital fluid resuscitation, facile transfer to the operating room, early detection of anatomy and pathology of the injury, an early decision to call for perfusion and cardiothoracic surgery, and prompt blood transfusion were the key factors that allowed for the patient to survive without deficits.